USING YOUTUBE VIDEOS TO ENHANCE THE EFL STUDENTS’ VOCABULARY MASTERY - Robi Soma (Didascein : Journal of English Education, 2025)
Vocabulary is one of the important elements of language. It supports students to be able to master four skills in English. YouTube Videos as a digital-based learning medium can demonstrate language skills better than using audio, which is usually used in conventional teaching. This research aimed to find out whether students who were taught using YouTube videos could improve their vocabulary mastery compared to students who were not taught using YouTube videos. This research used a quantitative approach with a quasi-experimental design. The samples used in this research were students in Class VIII C and VIII D. To collect the data, the researcher used the research instrumentation in the form of vocabulary to measure the students’ prior knowledge before the treatment and to see the students’ treatment results. Furthermore, to analyze the data, the researcher used the t-test. Based on the results collected after conducting this research, the results of the research showed that there was a significant effect of using YouTube videos on vocabulary mastery in students in the experimental class. Students’ English vocabulary learning using YouTube videos was more effective than without using the conventional way of teaching vocabulary. In conclusion, YouTube videos could be used as an alternative way to teach vocabulary to EFL students, especially in the Indonesian context.